2012
DOI: 10.1016/j.foodres.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Dietary enrichment of eggs with omega-3 fatty acids: A review

Abstract: The health benefits of omega-3 polyunsaturated fatty acids (n−3 PUFA) are generally recognized. Unfortunately, in most western countries, the recommended daily intake of these compounds is rarely met. Therefore, enrichment of commonly occurring foods can boost intake of these fatty acids. In this regard, eggs are an interesting target, as they form an integral part of the diet. Their n−3 PUFA profile can be modified through feed supplementation. A traditional n−3 PUFA source to be added to hens' diet is flaxse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
213
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 225 publications
(221 citation statements)
references
References 63 publications
(156 reference statements)
4
213
1
3
Order By: Relevance
“…Are resulting eggs (a) acceptable and (b) offering a health benefit to consumers? A recent review article on dietary enrichment of eggs with n-3 fatty acids Fraeye et al (6) compares twenty-six studies using linseed, fish oils and/ or micro-algae as the source of n-3 PUFA, conducted between 1991 and 2011. One striking feature of the studies covered in this review is the diversity in the PUFA content reported in eggs from hens on the control treatments, reflecting variability in what might be considered as baseline diets, with respect to both n-3 and n-6 supply.…”
Section: Eggsmentioning
confidence: 99%
See 4 more Smart Citations
“…Are resulting eggs (a) acceptable and (b) offering a health benefit to consumers? A recent review article on dietary enrichment of eggs with n-3 fatty acids Fraeye et al (6) compares twenty-six studies using linseed, fish oils and/ or micro-algae as the source of n-3 PUFA, conducted between 1991 and 2011. One striking feature of the studies covered in this review is the diversity in the PUFA content reported in eggs from hens on the control treatments, reflecting variability in what might be considered as baseline diets, with respect to both n-3 and n-6 supply.…”
Section: Eggsmentioning
confidence: 99%
“…The response to supplementation, especially with linseed feeding, was greater if the control diet produced eggs low in n-3. Fraeye et al (6) suggest that dietary n-6 supply is also important as was the type or strain of hens, since their ability to convert ALA to longer chain n-3 varies with genetics and the age of the birds, as well as the relative competition between n-3 and n-6. Most studies covered in the present paper supplemented or substituted diets with linseed (high in ALA), fish oil (high in long-chain n-3 such as EPA and DHA) and/or heterotrophic micro algae (cultured 'seaweeds' also high in long-chain n-3 such as EPA and DHA), all of which appear to increase the n-3 content of eggs and reduce their n-6 concentrations.…”
Section: Eggsmentioning
confidence: 99%
See 3 more Smart Citations